The Correlation between Students’ Metacognitive Awareness and Their Anxiety in Writing Performance - Aglina, Evi Fitri; Rohmatillah, Rohmatillah; Syamsiah, Nur (Universitas Islam Negeri Raden Intan Lampung, 2020)
The aim of this study is to verify the relationship between students’ metacognitive awareness and their writing anxiety. The researchers used descriptive statistics and the Pearson’s correlation coefficient to find out the relation. Data were collected by distributing two questionnaires, Metacognitive Awareness Inventory (MAI) and Second Language Writing Anxiety Inventory (SLWAI) to 27 students who were at intermediate level and taking Academic Writing subject in English Department of State Islamic University of Raden Intan Lampung. The data were analyzed using SPSS. From the results, itrevealed that there was a significant correlation between students’ metacognitive awareness and their writing anxiety. The finding proved that Metacognitive awareness played a necessary role in increasing students’ writing performance by reducing the anxious feeling in the writing activities